Kinetics of In Vitro Inhibition of Acetylcholinesterase by Nineteen New Carbamates - Kovarova, Marketa; T.H. Khan, Mahmud; Komers, Karel; Parík, Patrik; Cegan, Alexander; Zatloukalova, Martina (Current Enzyme Inhibition, 2011)
Two series A and B of 12 and 7 new carbamate derivates were tested in vitro as acetylcholinesterase inhibitors. The tests were performed in the batch stirred reactor at 25°C, pH 8, ionic strength 0.11 M and catalytic activity of the enzyme preparation 0.14 U mL-1 of the reaction mixture. The temporal dependences of actual concentrations of acetylcholine, choline and acetic acid were determined by two independent analytical methods, HPLC and pH-stat. For all used inhibitors, the model of competitive irreversible inhibition was valid. The inhibition rate constant k3 and qualified estimation of the absolute acetylcholinesterase concentration in the reaction mixture were calculated. The partition coefficients Kow between n-octanol and water of all used inhibitors were determined. The k3 and Kow values were correlated with the Hammett and Hansch substituent constants and with the calculated docking and binding energies of the reaction between the tested inhibitors and acetylcholinesterase.
Keywords: enzymatic